2007
DOI: 10.1097/bpo.0b013e3181373ba8
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Triradiate Cartilage in Predicting Curve Progression in Adolescent Idiopathic Scoliosis

Abstract: Braces are commonly used to treat progressive adolescent idiopathic scoliosis. Several previous studies have reported a correlation between the success of brace treatment and skeletal maturity markers. These studies have not focused on the status of the triradiate cartilage (TRC) as it relates to successful brace treatment for adolescent idiopathic scoliosis. The authors retrospectively evaluated all patients at their institution from 1990 to 1997 with a diagnosis of adolescent idiopathic scoliosis who were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…The Risser + staging was an idea that came out during discussion when the importance of other radiographic signs like the tri-radiate cartilage was considered [ 30 , 42 , 43 ]. Many researchers in the SOSORT community use the so-called European Risser sign [ 28 - 30 ] that is born from a reported by Stagnara, a variation of the original Risser sign (here called US Risser sign).…”
Section: Discussionmentioning
confidence: 99%
“…The Risser + staging was an idea that came out during discussion when the importance of other radiographic signs like the tri-radiate cartilage was considered [ 30 , 42 , 43 ]. Many researchers in the SOSORT community use the so-called European Risser sign [ 28 - 30 ] that is born from a reported by Stagnara, a variation of the original Risser sign (here called US Risser sign).…”
Section: Discussionmentioning
confidence: 99%
“…Prognostically, patients with Risser 0- 2 are regarded as skeletally immature [ 34 ] and at high risk of progression. A recent study attempted to determine the influence of Risser sign on the need for surgery in children wearing orthoses for the treatment of AIS [ 35 ].…”
Section: Radiographymentioning
confidence: 99%
“…Interestingly, Ryan et al (2007) compared the curve progression rates of two groups of patients at Risser 0, one with tri-radiate cartilage open and another with the cartilage fused [ 34 ]. They found that the incidence of curve progression is higher in patients with open tri-radiate cartilage as opposed to those with closed tri-radiate cartilages [ 34 ].…”
Section: Radiographymentioning
confidence: 99%
See 1 more Smart Citation
“…This can be done clinically with serial measurements of overall standing and seated trunk height measurements with each office visit, Tanner staging, and recording the timing of menarche for female patients. Radiographic methods include obtaining a left hand radiographs for comparison with a Greulich and Pyle atlas, open or closed status of the triradiate cartilage, or with use of Risser staging of the iliac apophysis [12][13][14]. Of these three, the most commonly used clinically the Risser sign described in 1958 [15].…”
Section: Adolescent Idiopathic Scoliosismentioning
confidence: 99%